2018
DOI: 10.1111/aas.13157
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐operative fluid bolus for improved haemodynamic stability during minor surgery: A prospectively randomized clinical trial

Abstract: A fluid bolus prior to anaesthesia reduced the incidence of haemodynamic instability during induction of general anaesthesia. The total fluid volume was slightly greater in the intervention group compared to the control group (1370 ± 439 mL vs 1219 ± 483 mL, P = .007). We conclude that a defined fluid bolus can help stabilizing haemodynamics in patients undergoing general anaesthesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“… 15 Similarly, lower incidence (41.5 vs. 56.6%) of postinduction hemodynamic instability was seen with preinduction preloading of 8 mL/kg Ringer's acetate as compared with no preloading. 7 In our study, too, we observed a significant difference in the occurrence of hypotension (26.7 vs. 86.7%) with and without fluid preloading. An earlier study demonstrated preoperative volume loading with 8 mL/kg Ringer's lactate to be more effective than preinduction administration of ephedrine in maintaining hemodynamic stability during rapid-sequence induction with propofol without HR increase during intubation.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“… 15 Similarly, lower incidence (41.5 vs. 56.6%) of postinduction hemodynamic instability was seen with preinduction preloading of 8 mL/kg Ringer's acetate as compared with no preloading. 7 In our study, too, we observed a significant difference in the occurrence of hypotension (26.7 vs. 86.7%) with and without fluid preloading. An earlier study demonstrated preoperative volume loading with 8 mL/kg Ringer's lactate to be more effective than preinduction administration of ephedrine in maintaining hemodynamic stability during rapid-sequence induction with propofol without HR increase during intubation.…”
Section: Discussionsupporting
confidence: 52%
“… 1 6 One of the measures used to minimize postinduction hypotension is preloading with intravenous fluids. The effect of preanesthetic fluid loading on ameliorating postinduction hypotension is equivocal, with some studies showing reduction in the incidence of hypotension with preanesthetic fluid loading, 7 while others observing no beneficial effect. 8 Therefore, for better understanding of postinduction hypotension, it is important to evaluate its mechanisms and assess the impact of fluid preloading by going beyond the routine blood pressure (BP) measurements and studying the advanced cardiac and hemodynamic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Administration of crystalloid preload before or during induction has some, but limited, effect on reducing the incidence of hemodynamic instability. 11,12 Increasing the injection time did not attenuate blood pressure reduction. 13 The use of bispectral cerebral monitoring (BIS) as a titration tool may not lower the induction dose or the incidence and degree of arterial hypotension.…”
Section: Introductionmentioning
confidence: 86%
“…Intravenous fluid administration remains the most common intervention to support cardiac output, arterial blood pressure and tissue perfusion in haemodynamically compromised patients . The administration of a bolus of fluid prior to the induction of anaesthesia is widely practiced to mitigate post‐induction arterial hypotension . The optimal strategy for fluid administration to maintain intravascular volume remains controversial with an accumulating body of evidence suggesting that inappropriate fluid therapy is associated with increased mortality and morbidity .…”
Section: Introductionmentioning
confidence: 99%